The Management of Needlestick Injuries - Himmelreich, Heiko (Deutscher Arzte Verlag, 2013)
BACKGROUND: An estimated 1 million needlestick injuries (NSIs) occur in Europe each year. The Council Directive 2010/32/EU on the prevention of NSIs describes minimum requirements for prevention and calls for the implementation of local, national and Europe-wide reporting systems. The Directive is to be implemented by all EU member states by 11 May 2013. The purpose of this study was to assess (and improve) the procedures for the reporting and treatment of needlestick injuries in a German tertiary-care hospital. METHODS: We carried out a prospective observational study of the NSI reporting system in the hospital over a period of 18 months and determined the incidence of NSIs, the prevalence of blood-borne pathogens among index patients, the rate of initiation of post-exposure prophylaxis, and the rate of serological testing of the affected health care personnel. RESULTS: 519 instances of NSI were reported to the accident insurance doctor over the period of the study, which consisted of 547 working days. 86.5% of the index patients underwent serological study for hepatitis B and C (HBV and HCV) and for the human immune deficiency virus (HIV); this resulted in two initial diagnoses (one each of active hepatitis B and hepatitis C) in the index patient. 92 of 449 index patients, or one in five, was infected with at least one blood-borne pathogen. HIV post-exposure prophylaxis was initiated in 41 health care workers. One case of hepatitis C virus transmission arose and was successfully treated. Other than that, no infection was transmitted. CONCLUSION: Complete reporting of NSIs is a prerequisite for the identification of risky procedures and to ensure optimal treatment of the affected health care personnel. The accident insurance doctor must possess a high degree of interdisciplinary competence in order to treat NSI effectively.